Melawan Korupsi: Inspirasi dari Injil Matius 6: 11 - Andreas Maurenis Putra (Societas Dei: Jurnal Agama dan Masyarakat, 2022)
This theological reflection wants to give a message to Christians by analyzing corruption based on the Gospel of Matthew 6:11 among the corruption proliferation in Indonesia. Through the library method, this article finds that Matthew 6:11 is against corruption because corruption is a form of ignorance to take care the social faith that inherited from Jesus, namely an attitude of being aware and caring for the others’ needs as reflected for “our food” and “enough” calling. Based on these findings, this article arrives at an alternative solution, it is promoting informal and formal anti-corruption education. Informally, parents are invited to build an example of honest living as a family habit and make the house as a faith school . Formally, it is necessary to integrate anti-corruption values ​​into a number of subjects or courses (inclusive approach) and make anti-corruption education into a local content subject or a separated subject (exclusive approach).